Translation Of Verses In Praise Of Prophet Muhammad(PBUH) In The Light Of Dr.Khan And Darya Abadi’S English Translations (A Comparative Linguistic Analysis) - Dr. Shair Ali Khan; Sidra Mehmood (Seerat Studies, 2023)
This article deals with the translation of the verses revealed in praise of Prophet Muhammad (Peace Be Upon Him). The study is limited to the English translations of two legendary Quran Translators: Dr Mohsin Khan and Abdul Majid Daryaabadi. The researchers, further, limitized the study to the verses which have been revealed in praise of Prophet Muhammad (Peace Be Upon Him). The selection of verses has been done through random method of selection. The researchers firstly analyzed grammatically all the verses as mentioned in the books of Quranic declension. Then analyzed the structure of Quranic sentences and translated sentences of both translations finding out the differences, equivalences, deep and surface structure of the translated sentences. The study is qualitative in nature.